Impact of veterinary pharmaceuticals on environment and their mitigation through microbial bioremediation - Saeed, Humaira; Padmesh, Sudhakar; Singh, Aditi; Nandy, Abhishek; Singh, Sujit Pratap; Deshwal, Ravi K. (Frontiers in Microbiology, 2024)
Veterinary medications are constantly being used for the diagnosis, treatment, and prevention of diseases in livestock. However, untreated veterinary drug active compounds are interminably discharged into numerous water bodies and terrestrial ecosystems, during production procedures, improper disposal of empty containers, unused medication or animal feed, and treatment procedures. This exhaustive review describes the different pathways through which veterinary medications enter the environment, discussing the role of agricultural practices and improper disposal methods. The detrimental effects of veterinary drug compounds on aquatic and terrestrial ecosystems are elaborated with examples of specific veterinary drugs and their known impacts. This review also aims to detail the mechanisms by which microbes degrade veterinary drug compounds as well as highlighting successful case studies and recent advancements in microbe-based bioremediation. It also elaborates on microbial electrochemical technologies as an eco-friendly solution for removing pharmaceutical pollutants from wastewater. Lastly, we have summarized potential innovations and challenges in implementing bioremediation on a large scale under the section prospects and advancements in this field.